Tree Mortality After a Hot Drought: Distinguishing Density-Dependent and -Independent Drivers and Why It Matters - Crouchet, Sarah E.; Jensen, Jennifer; Schwartz, Benjamin F.; Schwinning, Susanne (Frontiers in Forests and Global Change, 2019)
Hot drought is a climate phenomenon that has lately received much attention for its potential to disrupt forest function worldwide. A sharp increase in tree mortality associated with this climate pattern are often cast as a disturbance, in which high temperature is responsible for causing exceptional rates of mortality. The alternative interpretation is simply that drought kills trees in a density-regulating manner and within the bounds of normal forest function. To evaluate the evidence for disturbance versus regulating dynamics, we conducted censuses across 30 plots in the Edwards Plateau region of central Texas, USA, four years after the hot drought of 2011. The purpose was to explain variation in population responses to drought, including crown mortality, resprouting rate and sapling survivorship in terms of physical site factors, community characteristics and local climate data. Through model selection analysis, we identified the most parsimonious binomial regression models for the three most common species. In Ashe juniper populations, overall crown mortality was 20% and all predictive factors indicated the influence of population-regulating dynamics. In live oak (Quercus virginiana & Q. fusiformis), which had a crown mortality rate of 23%, the influence of regulating factors was less prominent, but there was also no evidence that crown death was linked to heat exposure. However, resprouting in both species appeared to be inhibited by heat exposure, as was crown mortality in the understory species Texas persimmon (Diospyros texana). Along with overall high levels of sapling survivorship, these patterns suggest that Ashe juniper woodlands, despite having been relatively hard hit by the 2011 drought, are not particularly threatened by hot drought events, although some subordinate species may be. Density-regulating mechanisms of forest drought response are often underplayed, but they are far easier to represent in vegetation models than disturbance dynamics.